DPP-4 inhibitor therapy and bone fractures in people with Type 2 diabetes – A systematic review and meta-analysis - Mamza, Jil; Marlin, Carol; Wang, Cai; Chokkalingam, Kamal; Idris, Iskandar (Diabetes research and clinical practice, 2016)
•Oral glucose-lowering medications have different effects on bone metabolism.•The effect of DPP-4 inhibitor on the risk of developing bone fractures is unclear.•Meta-analysis was conducted on RCT studies to assess fracture risk of DPP-4 inhibitor.•No significant association of fracture events found with the use of DPP-4 inhibitor. Fracture risk is higher in older adults with Type 2 diabetes mellitus (T2DM). Oral glucose-lowering medications have different effects on bone metabolism. The purpose of this study is to appraise the evidence from literature and determine the effect of dipeptidyl peptidase-4 (DPP-4) inhibitor on the risk of developing bone fractures. Using Boolean search terms, the search strategy combined synonyms of ‘fracture’ and ‘DPP-4 inhibitor’. Comprehensive electronic databases which include EMBASE, MEDLINE, the EMA and the WHO ICTRP databases were searched for randomised controlled trial (RCT) studies which compared a DPP-4 inhibitor with an active comparator or placebo amongst patients with T2DM. Meta-analysis was performed to compare DPP-4 inhibitor with either an active comparator or a placebo. The outcome measure was the presence or absence of fracture. The search yielded 5061 records relating to fractures and DPP-4 inhibitor, from which 51 eligible RCTs were selected for meta-analysis (N=36,402). Thirty-seven (37) studies compared DPP-4 inhibitor with placebo (n=23,974), while fourteen (14) studies (n=12,428) compared DPP-4 inhibitor with an active comparator. The mean age of patients was 57.5±5.4years, the average glycated haemoglobin (HbA1c) was 8.2%, while the average BMI was 30±2kg/m2. Overall, there was no significant association of fracture events with the use of DPP-4 inhibitor when compared with placebo (OR; 0.82, 95% CI 0.57–1.16, P=0.9) or when DPP-4 inhibitor was compared against an active comparator (OR; 1.59, 95% CI 0.91–2.80, P=0.9). This study offers a larger, up-to-date review of the subject. The meta-analysis showed that there was no significant association between DPP-4 inhibitor use and the incidence of fractures.